Flow characterization near the nozzle exit of the supersonic steam jet injecting into the stagnant water - KHAN, AFRASYAB; Sanaullah, Khairuddin; Mohammed Zwawi; Mohammed Algarni; Bassem F. Felemban; Ali Bahadar; Ahmed Salam Farooqi; Andrew Ragai Henry Rigit; Atta Ullah (Kuwait Journal of Science, 2021)
Injection of supersonic steam into a subcooled water has vital significance mainly due to the safety measures in water-cooled nuclear power plants, where it acts as a heat sink to discharge the steam as part of Reactor Coolant System (RCS), the phenomena occur here is Direct Contact Condensation (DCC). There has been a large amount of work being conducted on the thermo-dynamics of the DCC; however, not much attention was given to the phenomena particular active near the steam’s nozzle exit. To characterize the flow dynamics within the region adjacent to the steam’s nozzle exit, an experimental study was conducted. A transparent rectangular upright duct of 4 ft high, was built with a supersonic nozzle positioned at the bottom of the channel. Particle image velocimetry was applied to draw information on the steam’s jet penetration into the water as well as the entrainment and mixing between the two phases under the steam’s inlet pressure ranging from 1.5 – 3.0 bars. Here, flow dynamics was looked thoroughly within the region close to the exit of the supersonic steam’s exit. The region was characterized by normalized velocity and the normalized vertical, and radial distances, the jet’s mid velocity (Ue) at nozzle exit and nozzle exit dia (De) were the normalizing factors respectively. PIV normalized contour measurements depicted the change in radial velocity of the jet was small. Wheres, in the core region of the jet, the change in the jet’s velocity was not much till Y/De 4.3 and vertical velocity of the jet decreased slowly till Y/De 8. The jet’s normalized upward velocity attained an optimized value between Y/De 8 and Y/De 9.8. With varying pressures, 1.5 bars to 3.0 bars, the jet expanded radially in water. It was also found in the near nozzle exit region, the shear layer’s thickness remained within 0.2 – 0.5 De over the 1.5 – 3.0 bars pressure. Probability Density Function (PDF) analysis of Reynolds shear and normal stresses, confirmed that the velocity fluctuations across the shear layer originated because of the existence of the large eddies among the steam-water interface and the resulting profiles were Gaussian.